LEGAL DRAFTING PERDES BAGI BADAN PERMUSYWARATAN DESA (BPD) CANGKOL DAN KRAGILAN - , Mulyanto, Bambang Joko Sudibyo (PARENTAL, 2014)
Abstract Alpha The purpose of community service is to improve the understanding and competence of the members of the BPD Cangkol and BPD Kragilan, MojoKragilan district, Sukoharjo village as the legislature in order to construct a village regulation especially their main duty formulation editorial article by article in the Regulation of the village according to the concept of legal drafting drafting legal products villages. In addition, to enhance their knowledge and skills in using information technology to facilitate records management regulations village. Method of implementation activities through legal drafting practice to dissect the anatomy of the village in particular Regulation formulation technique editorial article by article. Keywords:Â  legal drafting, village, regulation.